2020
DOI: 10.1021/acs.energyfuels.0c00114
|View full text |Cite
|
Sign up to set email alerts
|

Modeling CO2 Solubility in Water at High Pressure and Temperature Conditions

Abstract: CO 2 dissolution in water at different temperature and pressure conditions is of essential interest for various environmental, geochemical, and thermodynamic related problems. The topic is of special interest in studies of CO 2 geological sequestration in brine-bearing aquifers. In this Article, four powerful machine learning (ML) techniquesRadial Basis Function Neural Network (RBFNN), Multilayer Perceptron (MLP), Least-Squares Support Vector Machine (LSSVM), and Gene Expression Programming (GEP)are implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(17 citation statements)
references
References 115 publications
0
17
0
Order By: Relevance
“…3–9. The cross plot is a well‐known visual method to evaluate the predictive performance of different artificial intelligent techniques 34–36. The concentration of the symbols of these figures around the diagonal line confirmed that the proposed MLP model is an appropriate tool for estimating the tonnage of the main products of the olefin unit.…”
Section: Resultsmentioning
confidence: 63%
“…3–9. The cross plot is a well‐known visual method to evaluate the predictive performance of different artificial intelligent techniques 34–36. The concentration of the symbols of these figures around the diagonal line confirmed that the proposed MLP model is an appropriate tool for estimating the tonnage of the main products of the olefin unit.…”
Section: Resultsmentioning
confidence: 63%
“…On the country, CO 2 solubility in ILs represents an opposite behavior against critical pressure. In other words, CO 2 solubility lowers by increasing critical pressure (Hemmati-Sarapardeh et al, 2020;Menad et al, 2019;Mokarizadeh et al, 2020). In order to compare the experimental and predicted result values and check the physical validity of the proposed model, variation of CO 2 solubility in one ionic liquid ([bmim][Tf2N]) against input parameters of pressure and temperature was investigated in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…Average absolute relative error and root mean square error (RMSE) values of their proposed CSA-LSSVM model were 10.71% and 0.0011, respectively. Hemmati-Sarapardeh et al 43 investigated the solubility of CO 2 in water at high pressures and temperatures using four powerful machine learning techniques. In this study, Multilayer Perceptron (MLP), Radial Basis Function (RBF), Least-Squares Support Vector Machine (LSSVM), and Gene Expression Programming (GEP) models were developed using temperature and pressure as input data to estimate the solubility of CO 2 in water.…”
Section: Introductionmentioning
confidence: 99%